Exploit of oxalate and phytate from the oilseeds with phytase treated seeds for dietary improvement. (October 2021) - Handa, Vrishbhanu; Thakur, Kritika; Arya, Shailendra Kumar
Abstract: Oilseeds are known to be the prime source of vegetable oil and possess medicinal and nutritional properties. But some components like phytate and oxalate present in the oilseeds limit their benefits. So, in our study five major oilseeds which are soybean seeds, rapeseeds, sesame seeds, sunflower seeds, and linseeds were treated with the phytase enzyme. The concentration of phytate decreased by 25% in sunflower seeds, 60% in sesame seeds, 37% in soybean seeds, 21% in rapeseeds, and 30% in linseeds. However, the concentration of oxalate has shown diverse results as it was reduced by 85% in soybean seeds but increased by 60% and 46.6% in sunflower and sesame seeds respectively. The concentration of oxalate was almost negligible in linseeds and rapeseeds. Therefore, this study gives the knowledge for the appropriate intake of oilseeds, mainly soybean seeds to improve the dietary intake in the case of kidney stone patients. Highlights: To find out the oxalate and phytate contents in five major oilseeds. Treatment of oilseeds with phytase enzyme and analyze the results. The concentration of phosphate and oxalate were compared in all the seeds after phytase enzyme treatment. SEM analyses were performed on all the seeds to visualize the CaOx crystals.